Exploring the influence of oak barrel aging on the quality of Cabernet Sauvignon wine with a high ethanol content: Interactions with wood grain and toasting level - Yu Chen; Xingmeng Lei; Tianyuan Zhang; Hulin Chen; Lisa Tang; Yi Shang; Zhen Huang; Yuyang Song; Yi Qin; Dongqing Ye; Yanlin Liu (Food Chemistry: X)
This study investigated and addressed the harm caused by high ethanol levels (above 16 % vol) to the quality of industrial Cabernet Sauvignon wines through aging in oak barrels with three types of wood grains and three toasting levels. Our findings demonstrated that differences in chemical indexes between the initial and final wines were not entirely due to the oak barrels. Barrels with medium grains and heavy toasting stabilized the wine's colour and minimised the loss of red tones; this effect was associated with phenolic components. Wood-unrelated volatiles were responsible for the considerable variations in volatile profiles; these differences were characterised by a decrease in alcohols, alongside an increase in ethyl esters, enhancing the fruity and floral attributes of the final aged wines. High-ethanol wines aged in medium-grained and heavily toasted barrels exhibited the best characteristics. These findings provide information to address concerns that a high ethanol content compromises wine quality.